Legal Responsibility of Doctors for Misdiagnosis in the Era of Artificial Intelligence - Hardinata Hardinata; Asep Sapsudin (Research Horizon, 2026)
Artificial Intelligence (AI) integration in medical diagnostics has transformed healthcare services by improving diagnostic speed, accuracy, and efficiency. However, the use of AI also raises complex legal issues concerning liability when misdiagnosis occurs and causes harm to patients. This study aims to analyze the forms of legal responsibility arising from AI-assisted medical misdiagnosis and to formulate an ideal legal framework capable of ensuring legal certainty and patient protection in Indonesia. The research employs a normative juridical method with a descriptive-analytical approach through statutory and conceptual analyses. Data were collected through library research using primary, secondary, and tertiary legal materials related to health law, criminal law, medical malpractice, and AI governance. The findings reveal that legal responsibility in AI-assisted diagnosis encompasses civil, criminal, and administrative liability involving physicians, healthcare facilities, and AI developers. This study proposes a multi-layer liability model that proportionally distributes accountability according to each party’s role and control. The study concludes that adaptive and comprehensive AI regulations are urgently required to ensure patient safety, technological accountability, legal certainty, and sustainable innovation in digital healthcare services.